Dairy performance of Tharparkar, Holstein Friesian and their crosses - BHATTACHARYA, T K; PATIL, V K; JOSHI, J D; MAHAPATRA, A S; BADOLA, S (The Indian Journal of Animal Sciences, 2014)
Total lactational milk production, lactation lengtb and milk yield per day of lactation length of 41 India born Holstein Friesian, 110 Tharparkar, 214 F1, crossbred and 30 F2 crossbred cattle maintained at the Central Cattle Breeding Farm, Lakhimpur-Kheri, Uttar Pradesh, were studied. Analysis of variance technique was used to estimate the effect of nongenetic factors on lacation length and lactational milk yield. The average lactational milk yield in Holstein Friesian, Tharparkar, F1 crosses and F2 crosses were estimated as 2482.46±175.36, 1525.06±58.75, 2753.16±67.15 and 1747.99±169.65 kg, respectively, whereas the average lactation length and lactational milk yield/day of lactation length were observed as 295± 18.26, 279.67±9.99, 312.20±6.49 and 247.87±41.07 days, respectively, and 8.25± 19. 5.47±0.12, 8.71±0.13 and 6.65±0.39 kg/day, respectively. The effect of season on lactation length was significant in Tharparkar cattle and nonsignificant in Holstein Friesian, F1 and F2 crossbred animals. The effect of season on lactation milk yield were nonsignificant in all the breed groups. The effect of period on lactation length were significant in all breed groups of animals. The period affected lactational milk yield significantly in Tharparkar and F2 crossbred animals and nonsignificantly in Holstein Friesian and F1 crossbred cattle. The phenotypic association between lactation length with lactational milk yield and lactational milk yield with lactational milk yield per day of lactation length were in the range of 0.82±0.04 to 0.92±0.07 and 0.44±0.09 to 0.73±0.13, respectively, and statistically significant in all breed groups. The simple association between lactation length and lactational milk yield per day oflactation length were in the range of -0.04±0.1 0 to 0.4 7±0.17 in all the animals. In conclusion it may be stated that performance of F2 HF-Tharparkar crosses possibly be the best among indigenous, exotic and F2 crossbred animals maintained in the tropical climatic condition. As the production traits studied here are significantly associated amongst each other, anyone or few traits like lactation length or lactational milk yield may be used for further genetic analysis of animals.